Analisis Spasiotemporal Alih Fungsi Lahan Sawah Berdasarkan Citra Satelit dan Sistem Informasi Geografis di Kawasan Metropolitan Sarbagita, Bali - I Putu Sriartha; I Putu Gede Diatmika; I Wayan Krisna Ekaputra (Pusat Kajian Bali Universitas Udayana, 2019)
The development of Denpasar, Badung, Gianyar, and Tabanan into a metropolitan area that is called in short Sarbagita can threaten the existence of community rice field land and agrar- ian culture considering that around 32.3% of the rice field in Bali is situated in this area. This study aimed at finding out the accuracy of Pleiades and Ikonos satellite image in mapping rice field land conversion, and producing a spatiotemporal map of rice field land conversion. This study used a quantitative descriptive method through image interpretation, field valida- tion, and Geographical Information System (SIG) technique. The location of the study sample was in Badung Regency Sar- bagita Metropolitan area. The result showed that Ikonos and Pleiades satellite image has a 94.1% accuracy, which means that it falls into the very good category, so that it can be used for mapping rice field land conversion spatiotemporally. The spatiotemporal map produced shows that there has occurred a decrease in rice field area from 10,810.18 hectares in 2009 to 10,565.82 hectares in 2016. The rice field land conversion phe- nomenon tends to shift from that which was previously domi- nant in the south part to that in the north part.